Olympic preparation camps 2000 - physical abilities testing - Sands, W. A. (Technique, 2000)
The longitudinal data from the Olympic Preparation Camp Series has shown a variety of trends. Because athlete participation from camp to camp was not certain, some of the tests involved different numbers of athletes. Injury, illness, and special circumstances also constrained athletes in their participation in specific tests. The number of athletes for each longitudinal analysis is shown with each figure. The results of these trends showed that the athletes gained and then lost mass while never returning to a body mass less than their initial measurements. The basic trends of all the strength-endurance tests indicated improvement throughout the camp series. Short-term power did not show improvement, largely due to the focus of training and conditioning on strength-endurance qualities. Future endeavors of this nature should attempt to continue this and other data collection in the process of determining optimal parameters for the conduct of athlete preparation up to Olympic Games and World Championships.